Survei status gizi atlet pencak silat Kota Makassar - Silatul Rahmi (Seminar Nasional LP2M UNM, 2019)
Nutritional status is important because it is one of the risk factors for the occurrence of pain and death. Good nutritional status in a martial arts athlete will contribute to his health and also to his ability in the recovery process. All nutrients needed by the body are contained in the food we eat everyday. Foods that meet the nutritional needs that are recommended by the MOH are 4 (four) healthy 5 (five) perfect, but the amount is of course adjusted to the needs of the individual concerned. For martial arts athletes who want to achieve their best performance through food and food patterns, both by reducing and increasing body weight according to the class of the match. A martial arts athlete tries to maximize his performance, and he is aware that any disruption to the body's system will prevent him. Athletes in general as human individuals need energy and motivation to need activities that have been done for physical training, therefore it is important for them to have attitudes and actions to maintain health conditions through consumption of food. In the environment of athletes sometimes for nutritional intake is not considered, they are only recommended for training so that the athlete's nutritional intake is not controlled. This is also related to knowledge, especially knowledge of nutrition, so that the way they fulfill their nutrition is different, meaning that they only eat and do not know whether the food or drink he consumes is not suitable for them.The purpose of this study was to determine the nutritional status of Makassar martial arts athletes. There is one variabel used in this study, namely nutritional status. The research design used in this study is descriptive. The population in this study was all of the urban makassat pencak silat athletes with a total of 20. The sampling technique used in this study was Non Random Sampling with the Quota Sapling technique, namely by assigning a number of sample quotum members or rations. From the results of the determination of the sample taken were 20 Pencak Silat Athletes in Makassar. The data analysis technique used is Percentage Descriptive statistics. The results obtained were 70% of Makassar city martial arts athletes with good nutritional status. Athletes must fill their bodies with carefully selected fuels, just like race cars with special fuels, apply the same logic to the engine, the athlete's body that functions properly is important for achieving optimal performance.